Fibroblast Growth Factor Receptor 4 Deficiency Mediates Airway Inflammation in the Adult Healthy Lung? - Easter, Molly; Garth, Jaleesa; Harris, Elex S.; Shei, Ren-Jay; Helton, Eric S.; Wei, Yuhua; Denson, Rebecca; Zaharias, Rennan; Rowe, Steven M.; Geraghty, Patrick; Faul, Christian; Barnes, Jarrod W.; et al. (Frontiers in Medicine, 2020)
Fibroblast growth factor receptor (FGFR) 4 has been shown to mediate pro-inflammatory signaling in the liver and airway epithelium in chronic obstructive pulmonary disease. In past reports, FGFR4 knockout (Fgfr4−/−) mice did not show any lung phenotype developmentally or at birth, unless FGFR3 deficiency was present simultaneously. Therefore, we wanted to know whether the loss of FGFR4 had any effect on the adult murine lung. Our results indicate that adult Fgfr4−/− mice demonstrate a lung phenotype consisting of widened airway spaces, increased airway inflammation, bronchial obstruction, and right ventricular hypertrophy consistent with emphysema. Despite downregulation of FGF23 serum levels, interleukin (IL) 1β and IL-6 in the Fgfr4−/− lung, and abrogation of p38 signaling, primary murine Fgfr4−/− airway cells showed increased expression of IL-1β and augmented secretion of IL-6, which correlated with decreased airway surface liquid depth as assessed by micro-optical coherence tomography. These findings were paralleled by increased ERK phosphorylation in Fgfr4−/− airway cells when compared with their control wild-type cells. Analysis of a murine model with constitutive activation of FGFR4 showed attenuation of pro-inflammatory mediators in the lung and airway epithelium. In conclusion, we are the first to show an inflammatory and obstructive airway phenotype in the adult healthy murine Fgfr4−/− lung, which might be due to the upregulation of ERK phosphorylation in the Fgfr4−/− airway epithelium.